THE ROLE OF CERTIFICATION IN PROMOTING SUSTAINABLE FOREST MANAGEMENT - Kiran Iqbal; Fatima Malik; Ahmed Shah (Journal of Selvicoltura Asean, 2025)
The increasing global demand for timber and forest products has raised concerns about unsustainable forest practices, resulting in deforestation, biodiversity loss, and ecosystem degradation. Certification programs, such as FSC (Forest Stewardship Council) and PEFC (Programme for the Endorsement of Forest Certification), have emerged as tools to promote sustainable forest management (SFM). These certifications aim to ensure that forests are managed in an environmentally responsible, socially beneficial, and economically viable manner. However, the effectiveness of certification in achieving these goals remains a topic of ongoing debate. This research aims to evaluate the role of forest certification programs in promoting sustainable forest management. Specifically, it investigates the impact of certification on forest practices, local communities, and the broader forest industry. A mixed-methods approach was adopted, combining qualitative interviews with forest managers, certification bodies, and local stakeholders, alongside quantitative analysis of forest management data in certified versus non-certified forests. Data were collected from various regions, including Southeast Asia, North America, and Europe. The findings reveal that certification programs positively influence forest management practices, leading to improved biodiversity conservation, better forest regeneration, and increased stakeholder engagement. However, challenges such as high certification costs, lack of awareness, and insufficient enforcement were identified as barriers to achieving full potential. Certification programs play a significant role in promoting sustainable forest management, though further efforts are needed to address barriers and enhance the inclusivity and effectiveness of these programs.